Identifikasi Komponen Minyak Atsiri Daging Buah Pala (Myristica Fraghans Houtt.) Asal Pulau Lemukutan dan Uji Aktivitas Antiinflamasi Menggunakan Metode Stabilisasi Menbran RBCs (Red Blood Cells) - Guntur Guntur; Harlia Harlia; Ajuk Sapar (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2019)
Nutmeg (Myristica fragrans Houtt) is a medicinal plant that produces essential oils and is often used as a flavoring of food and medicine. The process of extracting essential oils from the nutmeg fruit pulp using the steam-water distillation method. The yield of essential oil obtained at 0.07765%, with a pale yellow color, the distinctive smell of nutmeg oil with a refractive index of 1.485, and a specific gravity of 0.909 g / mL and soluble in ethanol. The results of GC-MS identification showed that the essential oil of nutmeg fruit flesh contains five components, the main compound is myristicin (18.44%), α-pinene (14.2%), limonene (9.37%), γ-terpinene (7.98%) and terpinolene (7.66%). Based on the test results of anti-inflammatory activity, the value of the percentage of red blood cell stability optimum mounting to 80.21% at a concentration of 10 ug / mL, where the standard aspirin has an activity of 72.26%. These results indicate that the meat nutmeg essential oil is potential as anti-inflammatory agents.